Life Satisfaction of US-trained Dental Specialists in Taiwan - Martin M. Fu; Rebecca Y. Chen; Min-Wen Fu; Huan-Chen Kao; Huan-Chiao Kao; Hsun-Liang Chan; Earl Fu; Tony Szu-Hsien Lee (International Dental Journal, 2022)
ABSTRACT: Objective: A large number of residents in US advanced specialty education programmes are foreign-trained dentists. When faced with the career dilemma of applying for US residency training, foreign-trained dentists may wonder whether it is worth proceeding along that path. In addiditon, studies capturing benefits from receiving US residency training are rare. Therefore, this study compared the life satisfaction amongst 3 dentist groups in Taiwan (ie, US-trained specialists, Taiwan-trained specialists, and general dentists). Methods: Cross-sectional surveys were distributed to dentists currently residing in Taiwan. Participants were surveyed about demographic information, career-related information, and life satisfaction. Life satisfaction was measured with a structured Satisfaction With Life Scale (SWLS). Nonparametric bivariate analyses and multivariable adjusted generalised linear model (GLM) were used to examine the differences between mean SWLS scores and examined variables. We included 134 US-trained specialists, 134 Taiwan-trained specialists, and 134 general dentists matched for age, sex, and marital status. Results: With the mean age of 51.4 ± 10.8 years old, specialists had significantly higher mean life satisfaction scores than general dentists. US-trained specialists had significantly higher mean life satisfaction scores than Taiwan-trained specialists when health and family relationships were not considered. Career-rated factors (eg, spending more clinical hours with patients, having more expenses related to continuing education, publishing more peer-reviewed articles, and being a frequent speaker) were not associated with better life satisfaction. Conclusions: US-trained specialists were more likely to be satisfied with their lives than Taiwan-trained specialists and general dentists. However, health and social relationships contribute more to dentists’ life satisfaction than do career-rated factors.